On periodicity of solutions for thermocontrol problems with hysteresis-type switches - Gurevich, Pavel; Jäger, Willi; Skubačevskij, Aleksandr Leonidovič (SIAM journal on mathematical analysis, 2009)
Mathematical models of thermocontrol processes occurring in chemical reactors and climate control systems are considered. In the models under consideration, the temperature inside a domain is controlled by a thermostat acting on the boundary. The feedback is based on temperature measurements performed by thermal sensors inside the domain. The solvability of the corresponding nonlinear nonlocal problems and the periodicity of solutions are studied.